Reformation, resistance, and reason of state (1517-1625) - Mortimer, Sarah; Oxford University Press (Oxford Oxford University Press, 2021)
This volume charts the development of political thought between 1517-1625. Drawing on a wide range of sources from Europe and beyond, it offers a new reading of early modern political thought, making connections between Christian Europe and the Muslim societies that lay to its south and east.
Keywords: Geschichte 1517-1625; Reformation -- Europe; Political Science -- History -- 16th century -- Europe; Ideologie; Politische Theorie; Politische Wissenschaft; Politisches Denken; Reformation; Europe -- Politics and government -- 1517-1648; Europe -- Civilization -- 16th century; Electronic books